2017
DOI: 10.1093/hsw/hlx018
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Social Participation on the Relationship between Incontinence and Depressive Symptoms in Older Chinese Women

Abstract: Urinary and fecal incontinence affect older women's social participation and mental health. This study examined the relationship between incontinence severity and depressive symptoms, focusing on the mediating effect of social participation, based on secondary analysis of structured interview data collected in December 2010 from 467 women age 60 and over in mainland China. Incontinence was significantly and positively associated with depressive symptoms but negatively associated with social participation. Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
2
1
1
Order By: Relevance
“…In spite of the literature pointing out that UI leads to restrictions in social participation in our study participation was not a domain in which disability scores were significantly different between incontinent and nonincontinent women. In a study with older incontinent Australian women, the authors found an association between UI and social dysfunction, but they pointed out that this association is not casual; in fact, it is a reflection of general health and overall functioning level of women, exploring a new axis of discussion about this domain and approaching the influence of environmental aspects on it.…”
Section: Discussioncontrasting
confidence: 93%
“…In spite of the literature pointing out that UI leads to restrictions in social participation in our study participation was not a domain in which disability scores were significantly different between incontinent and nonincontinent women. In a study with older incontinent Australian women, the authors found an association between UI and social dysfunction, but they pointed out that this association is not casual; in fact, it is a reflection of general health and overall functioning level of women, exploring a new axis of discussion about this domain and approaching the influence of environmental aspects on it.…”
Section: Discussioncontrasting
confidence: 93%
“…hearing difficulties) limit social engagement and civic activities (e.g. volunteering) [7, 32, 3438]. Individual characteristics such as age might influence health effects on activity participation.…”
Section: Introductionmentioning
confidence: 99%
“…China now boast the world's largest Internet population of 854 million [15], and online participation has become a common method for Chinese citizens to contact political authority and articulate their issues and grievances [16,17]. Moreover, researchers have paid more and more attention to social participation of some specific disadvantaged groups, including older adults [18,19], disabled groups [20,21], and migrant workers [22,23] et al Similar to the findings of other countries, many researches confirm that social participation contributes to Chinese health [24], including mental health [25,26], and political trust [27]. However, as another relatively vulnerable group (due to the separateness of their onboard and shorebound lives), merchant sailors' social participation has been seldom examined and is little known in the Chinese context, although China has the largest population of registered sailors in the world [28].…”
Section: Introductionmentioning
confidence: 99%